Use of local infiltration and vasoconstrictors in vaginal surgery - Yeasmin, Syeda Farzana; Hasanat, Md Abul; Rahman, Md Tuhitur; Islam, Farhana; Akhtar, Dalia; Begum, Arifa (Mediscope, 2019)
Background: Lidocaine Adrenaline Combination (LAC) in saline (Jungle juice) is used to provide perioperative analgesia, blood conservation and separation of tissue planes. It comprises 20 ml of 2% lidocaine, 80 ml of sterile saline and 0.5 ml of 1:1000 adrenaline solution. This study aimed to evaluate knowledge and safe usage of jungle juice on patients. Objective: To stablish formulation, extent of usage, patterns & safety measures employed during use of jungle juice among surgical teams. Methods: This prospective case control study was carried out in Obstetrics & Gynecology department of Ad-din Akij Medical College & Hospital, Khulna from March 2014 to June 2018. Patients were divided into two groups. In the control group, no paracervical infiltration was given. In the experimental group, paracervical infiltration was given before hysterectomy. The operating time, blood loss and post-operative infection were noted in each group. Results: The mean operating time was higher (59.18 minutes) in vaginal hysterectomy and 60.93 minutes in fistula & perineal repair surgery without infiltration in comparison to the group with infiltration (P<0.05). There was significant difference in haemoglobin concentration & amount of blood loss after surgery between the groups. There was no case of infection in both groups. Conclusions: From our study, we concluded that paracervical infiltration provide perioperative analgesia, blood conservation & separation of tissue for ease of dissection. Mediscope Vol. 6, No. 2: Jul 2019, Page 49-52